KNOWLEDGE AND PRACTICES OF MIDWIVES REGARDING ZIKA VIRUS IN KENDARI, SOUTHEAST SULAWESI, INDONESIA - Tosepu, Ramadhan; Nisa Patawari, Indri Eka Artamevia Khaerun; Lestari, Hariati; Karimuna, Siti Rabbani; Sety, La Ode Muhamad; Nirmala, Fifi (YCAB Publisher & IAKMI SULTRA, 2020)
Background: In 2016 Zika virus infection became an international public health emergency concern.Objective: This study aimed to evaluate the knowledge and practice of midwives regarding the Zika virus.Methods: This research was an analytic study with a cross-sectional approach. A total of samples was 191 selected using a proportional random sampling technique. WHO questionnaire was used to collect data on knowledge and practice related to the Zika virus and a set of explanatory variables.Results: The midwife's knowledge of the Zika virus revealed that only the workplace and sources of information were associated with knowledge of the Zika virus infection. Public health center had a greater chance of having good knowledge than hospitals with OR: 5.130 (CI: 2.591-10.157) and first knew Zika information more than one year ago had a greater chance of having good knowledge than the first midwife knew about Zika on the day the study was conducted with OR: 3.035 (CI: 1.485-6.203).Conclusion: Knowledge and practice regarding Zika virus infection among midwives in Kendari city Indonesia was relatively good. Furthermore, midwives who work in the public health center had a five times chance compared to midwives who work in hospitals to have better knowledge related to the Zika virus.